Paracrine Secreted Frizzled-Related Protein 4 Inhibits Melanocytes Differentiation in Hair Follicle. (27th February 2017) - Guo, Haiying; Lei, Mingxing; Li, Yuhong; Liu, Yingxin; Tang, Yinhong; Xing, Yizhan; Deng, Fang; Yang, Ke
Abstract : Wnt signaling plays crucial role in regulating melanocyte stem cells/melanocyte differentiation in the hair follicle. However, how the Wnt signaling is balanced to be overactivated to control follicular melanocytes behavior remains unknown. Here, by using immunofluorescence staining, we showed that secreted frizzled-related protein 4 (sFRP4) is preferentially expressed in the skin epidermal cells rather than in melanocytes. By overexpression of sFRP4 in skin cells in vivo and in vitro, we found that sFRP4 attenuates activation of Wnt signaling, resulting in decrease of melanocytes differentiation in the regenerating hair follicle. Our findings unveiled a new regulator that involves modulating melanocytes differentiation through a paracrine mechanism in hair follicle, supplying a hope for potential therapeutic application to treat skin pigmentation disorders.